The Role of Facilitation in Praxis - Joseph A. Raelin (Organizational Dynamics, 2006)
The application of facilitation in organizational life has become so popular that it has been co-opted in some quarters as a basis for defining the managerial role. Although it has attributes that can be applied to human interactions across and within organizations, its practice is delimited within group settings as assisting members to accomplish their goals through a focus on process rather than on content. Within the world of praxis, which focuses on settings in which there is an explicit attempt to learn from reflection on action, facilitation is further defined as embodying a reflective practice that is concurrent with and critical of experience. In this article, facilitation will be characterized as a means of bringing out learning for both self and others within team settings. The account will review some of the explicit skills and interventions that facilitators need to deploy when the focus of attention is on praxis rather than on task accomplishment.
Keywords: M53; J52; M12; M14; M10; D23; 650; Facilitation; Dialogue; Praxis; Learning; Action learning; Action science